NIEWYDOLNOŚĆ SERCA I PŁUC, TRANSPLANTOLOGIANon adherence in heart transplant recipients - Pudlo, Robert; Jaworska, Izabela; Pacholewicz, Jerzy; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Insufficient doctor-patient co-operation is a serious medical problem resulting in prolonged hospitalization, a greater number of complications, increased treatment costs and even shortening of the patient’s life. In order to improve recipient care and prolong the recipients’ life, it is necessary to identify subgroups with an increased risk of disregarding doctor’s recommendations. Such recipients should remain in continuous contact with a psychologist, their check-up visits should be more frequent, and what is more, contact should be maintained with their families. Some risk factors, such as young age, are independent of both the patient and the doctor. As a rule, the co-operation worsens with the passage of time after transplantation, and is also weaker in individuals with diagnosed addictions and personality disorders. Finally, mental disorders, especially depression, have a rapid but periodic negative impact on the doctor-patient co-operation. Early diagnosis and consistent treatment of such disorders is vitally important. It is true for all patients that better contact and greater knowledge concerning numerous aspects of the patient’s life reduce threats resulting from lack of co-operation.